Adhesive composition comprising a polyurethane and a cationic dopant

CN117625109BActive Publication Date: 2026-10-27E INK CORP
View PDF 54 Cites 0 Cited by

Patent Information

Application Number
CN202311757509.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-07
Filing Date
2020-08-26
Publication Date
2026-10-27
Estimated Expiration
2040-08-26

AI Technical Summary

Benefits of technology

[0047]以下的详细说明描述本发明的其他方面和各种非限制实施方案。在本说明书和通过引用并入的文件包括冲突和/或不一致的公开内容的情况下,应以本说明书为准。如果以引用方式并入的两个或更多个文件包括相互冲突和/或不一致的公开内容,则以生效日期较晚的文件为准。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117625109B_ABST
    Figure CN117625109B_ABST
Patent Text Reader

Abstract

An adhesive composition comprising a polyurethane and a cationic polymeric dopant or a polymerizable cationic dopant, which can be used to form one or more adhesive layers of an electro-optical assembly. They improve the electro-optical performance of the corresponding electro-optical device even at low temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with priority date of October 7, 2019, application number 202080063819.6, entitled "Adhesive composition comprising polyurethane and cationic dopant".

[0002] Related applications

[0003] This application claims priority to U.S. Provisional Application No. 62 / 911,742, filed October 7, 2019, which is incorporated herein by reference in its entirety. Background of the Invention

[0004] This invention relates to adhesive compositions comprising polyurethane and cationic polymeric dopants or polymerizable cationic dopants. The adhesive compositions can be used to form adhesive layers in electro-optical components, improving electro-optical performance even at low temperatures.

[0005] The term "electro-optic," used herein for materials, devices, displays, or components, is used in its conventional sense in the field of imaging to refer to a material having a first display state and a second display state that differ in at least one optical property, said material changing from its first display state to its second display state by applying an electric field to the material. While the optical property is generally color perceptible to the human eye, it can also be other optical properties such as optical transmittance, reflectance, brightness, or, in the case of a display intended for machine reading, false color in the sense of a change in reflectance at electromagnetic wavelengths outside the visible light range. The terms "electro-optic device" and "electro-optic display" are considered synonymous herein. The term "electro-optic assembly," as used herein, can refer to an electro-optic device. It can also refer to multilayer components used to construct an electro-optic device. Thus, for example, a front-panel laminate described below is also considered an electro-optic assembly.

[0006] The term "gray state" is used herein in its conventional sense within the field of imaging to refer to a state intermediate between two extreme display states of a pixel, and does not necessarily imply a black-to-white transition between these two extreme states. For example, many of the E Ink patents and published applications described below describe electrophoretic displays where the extreme states are white and dark blue, making the intermediate "gray state" actually light blue. In fact, as already mentioned, the change in display state may not be a color change at all. The terms "black" and "white," as used below, refer to the two extreme display states of a display, and should be understood to generally include extreme display states that are not strictly black and white, such as the white and dark blue states mentioned above. The term "monochrome," as used below, refers to a driving scheme that drives pixels only to their two extreme display states without an intermediate gray state.

[0007] In the sense that a material has a solid outer surface, some electro-optic materials are solid, although the material may and often does indeed have an internal space filled with liquid or gas. Such displays using solid electro-optic materials may, for convenience, be referred to below as "solid-state electro-optic displays." Therefore, the term "solid-state electro-optic display" includes rotating dual-color component displays, encapsulated electrophoretic displays, microporous electrophoretic displays, and encapsulated liquid crystal displays.

[0008] The terms “bistable” and “bistable” are used herein in their conventional sense in the art to refer to a display comprising display elements having a first display state and a second display state that are different in at least one optical property, such that after any given element has been driven to present its first or second display state by an addressing pulse of finite duration, the state will persist for at least several times, for example, at least four times, the minimum duration of the addressing pulse required to change the state of the display element after the addressing pulse has terminated. U.S. Patent No. 7,170,670 shows that some particle-based electrophoretic displays capable of having grayscale are stable not only in their extreme black and white states but also in their intermediate gray states, as are some other types of electro-optical displays. Such displays are more appropriately referred to as “multistable” than bistable; however, for convenience, the term “bistable” may be used herein to encompass both bistable and multistable displays.

[0009] Many types of electro-optic displays are known. One type of electro-optic display is the rotating bicolor component type, as described, for example, in U.S. Patents Nos. 5,808,783, 5,777,782, 5,760,761, 6,054,071, 6,055,091, 6,097,531, 6,128,124, 6,137,467, and 6,147,791. Although this type of display is often referred to as a “rotating bicolor sphere” display, the term “rotating bicolor component” is preferred due to its greater accuracy, as in some of the aforementioned patents, the rotating component is not spherical. This display uses a large number of small individuals (generally spherical or cylindrical) having two or more portions with different optical characteristics and internal dipoles. These individuals are suspended within liquid-filled bubble bodies within a matrix, the liquid allowing the individuals to rotate freely. The appearance of the display is altered by applying an electric field to it, thus rotating the individuals to various positions and changing the portion of the individuals seen through the viewing surface. This type of electro-optic medium is generally bistable.

[0010] Another type of electro-optic display uses an electrochromic medium, such as an electrochromic medium in the form of a nanochromic film, which comprises electrodes at least partially formed of a semiconductive metal oxide and a plurality of reversibly color-changing dye molecules attached to said electrodes; see, for example, O'Regan, B. et al., Nature 1991, 353, 737; and Wood, D., Information Display, 18(3), 24 (March 2002). See also Bach, U. et al., Adv. Mater., 2002, 14(11), 845. This type of nanochromic film is also described, for example, in U.S. Patents 6,301,038, 6,870,657, and 6,950,220. This type of medium is also generally bistable.

[0011] Another type of electro-optic display is the electrowetting display developed by Philips, described in Hayes, RA et al., "Video-Speed ​​Electronic Paper Based on Electrowetting", Nature, 425, 383-385 (2003). U.S. Patent No. 7,420,549 shows that this electrowetting display can be bistable.

[0012] One type of electro-optic display is the particle-based electrophoretic display, which has been the subject of intensive research and development for many years. In this display, multiple charged particles move through a fluid under the influence of an electric field. Compared to liquid crystal displays (LCDs), electrophoretic displays offer advantages such as good brightness and contrast, wide viewing angles, bistable states, and low power consumption. Nevertheless, long-term image quality issues have hindered their widespread use. For example, the particles constituting an electrophoretic display tend to settle, resulting in a short lifespan for these displays.

[0013] As shown above, the electrophoretic medium requires the presence of a fluid. In most prior art electrophoretic media, this fluid is a liquid, but electrophoretic media can also be manufactured using gaseous fluids; see, for example, Kitamura, T. et al., "Electrical toner movement for electronic paper-like display," IDW Japan, 2001, Paper HCS1-1; and Yamaguchi, Y. et al., "Toner display using insulative particles charged triboelectrically," IDW Japan, 2001, Paper AMD4-4. See also U.S. Patents 7,321,459 and 7,236,291. When the medium is used in a direction that allows such sedimentation, such as in a case where the medium is configured in a vertical plane, such gas-based electrophoretic media appear to be susceptible to the same type of problems as liquid-based electrophoretic media due to particle sedimentation. In fact, particle sedimentation appears to be a more serious problem in gas-based electrophoresis media than in liquid-based electrophoresis media, because the lower viscosity of gaseous suspensions compared to liquid suspensions allows electrophoretic particles to settle more rapidly.

[0014] Numerous patents and applications assigned to or in the name of the Massachusetts Institute of Technology (MIT), E Ink Corporation, E Ink California, LLC, and related companies describe various techniques for encapsulated and microporous electrophoretic and other electro-optic media. Encapsulated electrophoretic media comprise a plurality of small capsules, each containing an inner phase with particles electrophoretically moving in a fluid medium and a capsule wall surrounding the inner phase. Generally, the capsules themselves are held within a polymeric binder to form a coherent layer between two electrodes. In microporous electrophoretic displays, charged particles and fluid are not encapsulated within microcapsules but are retained within a carrier medium, typically a polymeric film, forming multiple cavities. The term "microcavity electrophoretic display" may be used hereinafter to encompass both encapsulated and microporous electrophoretic displays. The techniques described in these patents and applications include:

[0015] (a) Electrophoretic particles, fluids, and fluid additives; see, for example, U.S. Patents 7,002,728 and 7,679,814.

[0016] (b) Encapsulation, adhesives, and encapsulation methods; see, for example, U.S. Patents 6,922,276, 7,184,197, and 7,411,719.

[0017] (c) Microporous structures, wall materials, and methods for forming micropores; see, for example, U.S. Patents 7,072,095 and 9,279,906.

[0018] (d) Methods for filling and sealing micropores; see, for example, U.S. Patents 7,144,942 and 7,715,088.

[0019] (e) Films and subassemblies containing electro-optic materials; see, for example, U.S. Patents 6,982,178 and 7,839,564.

[0020] (f) Back panel, adhesive layer, and other auxiliary layers and methods for display; see, for example, U.S. Patents 7,116,318, 7,535,624, 7,012,735, and 7,173,752.

[0021] (g) Color formation and color adjustment; see, for example, U.S. Patents 7,075,502 and 7,839,564.

[0022] (h) A method for driving a display; see, for example, U.S. Patents 7,012,600 and 7,453,445.

[0023] (i) Applications of displays; see, for example, U.S. Patents 7,312,784 and 8,009,348.

[0024] (j) Non-electrophoretic displays, as described in U.S. Patent No. 6,241,921 and U.S. Patent Application Publication No. 2015 / 0277160; and applications of encapsulation and microvia technologies other than displays; see, for example, U.S. Patent Application Publications Nos. 2015 / 0005720 and 2016 / 0012710.

[0025] Many of the aforementioned patents and applications recognize that the walls surrounding the separated microcapsules in an encapsulated electrophoretic medium can be replaced by a continuous phase, thus creating a so-called polymer-dispersed electrophoretic display. In such a display, the electrophoretic medium comprises a plurality of separated droplets of electrophoretic fluid and a continuous phase of polymeric material. The separated droplets of electrophoretic fluid within such a polymer-dispersed electrophoretic display can be considered as capsules or microcapsules, even without a separating membrane connecting each individual droplet; see, for example, U.S. Patent No. 6,866,760. Therefore, for the purposes of this application, such polymer-dispersed electrophoretic media are considered a subclass of encapsulated electrophoretic media.

[0026] Although electrophoretic media are often opaque (because, for example, in many types of electrophoretic media, particles substantially block visible light from passing through the display) and operate in reflective mode, many types of electrophoretic displays can operate in so-called "shutter mode," where one display state is substantially opaque and the other is translucent. See, for example, U.S. Patents 5,872,552, 6,130,774, 6,144,361, 6,172,798, 6,271,823, 6,225,971, and 6,184,856. Dielectrophoretic displays, similar to electrophoretic displays but dependent on changes in electric field strength, can operate in a similar mode; see U.S. Patent 4,418,346. Other types of electro-optic displays can also operate in shutter mode. Electro-optic media operating in shutter mode are useful in multilayer structures of full-color displays, in which at least one layer adjacent to the viewing surface of the display operates in shutter mode to expose or conceal a second layer farther from the viewing surface.

[0027] Encapsulated electrophoretic displays generally do not suffer from the aggregation and sedimentation failure modes of conventional electrophoretic apparatus and offer further advantages, such as the ability to print or coat displays on a wide variety of flexible and rigid substrates. The term "printing" is intended to encompass all forms of printing and coating, including but not limited to: volumetric coating, such as patch die coating, slot or extrusion coating, ramp or step coating, curtain coating; roll coating, such as roller-blade coating, forward and reverse roll coating; gravure coating; dip coating; spray coating; meniscus coating; spin coating; brush coating; air knife coating; screen printing; electrostatic printing; thermal printing; inkjet printing; electrophoretic deposition (see U.S. Patent No. 7,339,715); and other similar techniques. Therefore, the resulting displays can be flexible. Furthermore, because the display media can be printed using various methods, it can be manufactured inexpensively.

[0028] Other types of electro-optic materials can also be used in this invention. Bistable ferroelectric liquid crystal displays (FLCs) known in the art are of particular interest.

[0029] In addition to the electro-optic material layer, an electrophoretic display generally includes at least two other layers disposed on opposite sides of the electro-optic material layer. One of these layers is an electrode layer. In most electro-optic devices, these layers are electrode layers, and at least one electrode layer is patterned to define a pixel of the device. For example, one electrode layer may be patterned as an elongated row electrode, and another may be patterned as an elongated column electrode extending perpendicularly to the row electrode, the pixel being defined by the intersection of the row and column electrodes. Alternatively and more generally, one electrode layer has the form of a single, continuous, light-transmitting electrode, and the other electrode layer is patterned as a pixel electrode matrix, each of which defines a pixel of the display. That is, one of these layers is generally a conductive, light-transmitting layer, and the other layer, generally referred to as a backplane substrate, contains a plurality of pixel electrodes configured to apply a potential between the conductive, light-transmitting layer and the pixel electrodes. In another type of electro-optic display intended for use with a stylus, the printhead or similar movable electrode is separate from the display, and only one of these layers adjacent to the electro-optic layer includes the electrode. The layer on the opposite side of the electro-optic layer is generally a protective layer intended to prevent the movable electrode from damaging the electro-optic material layer.

[0030] Fabricating a three-layer electro-optic display typically involves at least one lamination operation. For example, many of the aforementioned MIT and E Ink patents and applications describe a method for manufacturing an encapsulated electrophoretic display, wherein an encapsulated electrophoretic medium containing a capsule in an adhesive is coated onto a flexible substrate containing an indium tin oxide (ITO) or similar conductive coating (which serves as an electrode of the final display) on a plastic film, and the capsule / adhesive coating is dried to form a coherent layer of electrophoretic medium firmly adhered to the substrate. A backplate containing a pixel electrode array and conductors connecting the pixel electrodes to driving circuitry is then fabricated. To form the final display, the substrate with the capsule / adhesive layer on it is laminated to the backplate using a lamination adhesive. A very similar method can be used to fabricate an electrophoretic display usable with a stylus or similar movable electrode by replacing the backplate with a simple protective layer, such as a plastic film, on which a stylus or other movable electrode can slide. In a preferred form of this method, the backplate itself is flexible and is fabricated by printing the pixel electrodes and conductors onto a plastic film or other flexible substrate. The obvious lamination technique used to mass-produce displays via this method is roller lamination, which uses laminating adhesives. Similar manufacturing techniques can be used for other types of electro-optic displays. For example, microporous electrophoretic media or rotating dual-color component media can be laminated to a backplane in essentially the same manner as encapsulated electrophoretic media.

[0031] U.S. Patent No. 6,982,178 describes a method highly suitable for assembling solid-state electro-optic displays (including encapsulated electrophoretic displays) for mass production. This patent essentially describes a so-called “front panel laminate” (“FPL”) comprising, in sequence, a light-transmitting conductive layer, a layer of solid electro-optic dielectric, an adhesive layer, and a release sheet. Generally, the light-transmitting conductive layer is carried by a light-transmitting substrate, preferably flexible in the sense that the substrate can be manually wound onto a roller with a diameter of, for example, 10 inches (254 mm) without permanent deformation. The term “light-transmitting” is used in this patent and herein to mean that the layer is designed to transmit light sufficiently to allow a viewer to see through the layer to observe changes in the display state of the electro-optic dielectric, typically through the conductive layer and adjacent substrates (if present); where the electro-optic dielectric displays changes in reflectivity at non-visible wavelengths, the term “light-transmitting” should, of course, be interpreted as referring to the transmission of the relevant non-visible wavelengths. The substrate is generally a polymeric film, and typically has a thickness of about 1 to about 25 mil (25 to 634 micrometers), preferably about 2 to about 10 mil (51 to 254 micrometers). The conductive layer is conveniently a thin metal or metal oxide layer such as aluminum or ITO, or may be a conductive polymer. Poly(ethylene terephthalate) (PET) films coated with aluminum or ITO are commercially available, for example, “Aluminized Mylar” (“Mylar” is a registered trademark) from EIdu Pont de Nemours & Company in Wilmington DE, and good results can be obtained using this commercial material in the front-panel laminate.

[0032] Assembling an electro-optic display using this front-panel laminate involves removing the release sheet from the front-panel laminate and bringing the adhesive layer into contact with the backplate under conditions that effectively cause the adhesive layer to adhere to the backplate, thereby fixing the adhesive layer, electro-optic dielectric layer, and conductive layer to the backplate. This method is highly suitable for mass production because the front-panel laminate can be mass-produced (typically using roll-to-roll coating technology) and then cut into sheets of any size required for a specific backplate.

[0033] U.S. Patent No. 7,561,324 describes a so-called "double-sided release sheet" or "double-sided release film," which is essentially a simplified version of the front panel laminate of U.S. Patent No. 6,982,178 mentioned above. One form of double-sided release sheet comprises a layer of solid electro-optic dielectric sandwiched between two adhesive layers, one or both of which are covered by the release sheet. Another form of double-sided release sheet comprises a layer of solid electro-optic dielectric sandwiched between two release sheets. Both forms of double-sided release sheets are intended for use in a manner generally similar to the described method for assembling an electro-optic display from a front panel laminate, but involving two separate laminations; generally, in a first lamination, the double-sided release sheet is laminated to the front electrode to form a front sub-assembly, and then in a second lamination, the front sub-assembly is laminated to the back panel to form the final display, although the order of these two laminations can be reversed if desired.

[0034] As an alternative structure, U.S. Patent No. 7,839,564 describes a so-called "reverse front-plate laminate," a variant of the front-plate laminate described in U.S. Patent No. 6,982,178. This reverse front-plate laminate sequentially includes at least one of a light-transmitting protective layer and a light-transmitting conductive layer, an adhesive layer, a solid electro-optic dielectric layer, and a release sheet. This reverse front-plate laminate is used to form an electro-optic display having a laminated adhesive layer between the electro-optic layer and the front electrode or front substrate; a second adhesive layer may or may not be present between the electro-optic layer and the backplate, and is generally a thin adhesive layer.

[0035] One of the performance standards for electro-optical components is the temperature window for effective switching between different display states. Typically, switching efficiency decreases as the operating temperature decreases. The inventors of this invention have unexpectedly discovered that electro-optical devices using a binder layer formed from a composition comprising polyurethane and a type of cationic polymeric dopant or a type of polymerizable cationic dopant exhibit improved electro-optical switching performance at low temperatures. Invention Overview

[0036] Aspects of the present invention relate to adhesive compositions and electro-optical components and front panel laminates comprising such adhesive compositions.

[0037] In one aspect, the present invention provides an adhesive composition comprising polyurethane and a cationic polymeric dopant, said cationic polymeric dopant being represented by formula I.

[0038]

[0039] R3, R4, and R5 are independently alkyl or alkenyl groups with chains having 1 to 30 carbon atoms, or -(CH2). b-Q2-R2 group, wherein b is 2 to 5; R1 and R2 are independently selected from hydrogen, alkyl groups having chains of 1 to 30 carbon atoms, aryl groups, -OH, -SH, -NH2, -NHR1' and -NR1'R1"; Q1 and Q2 are independently selected from ethylene oxide, polyethylene oxide, propylene oxide, polypropylene oxide and mixtures thereof, wherein polyethylene oxide has a total of 2 to 100 ethylene oxide units and polypropylene oxide has 2 to 100 propylene oxide units; R1' and R1" are alkyl groups having chains of 1 to 30 carbon atoms; the number average molecular weight of the cationic moiety of the cationic polymer dopant is from about 400 Daltons to about 25,000 Daltons; and Y n- The counter ion is a polyatomic anion containing at least two fluorine atoms; and n is 1 to 6. The counter ion may contain at least three fluorine atoms.

[0040] In another aspect, the present invention provides an adhesive composition comprising polyurethane and a polymerizable cationic dopant, said polymerizable cationic dopant being represented by Formula II.

[0041]

[0042] Where R9 is a hydrogen or methyl group, R10 is an alkyl group having 1 to 10 carbon atoms, q is 1 to 5, and Y n- The counter ion is a polyatomic anion containing at least two fluorine atoms; and n is 1 to 6.

[0043] In another aspect, the present invention provides an electro-optic component comprising, in sequence: a conductive transparent layer, an electro-optic material layer, a first adhesive layer, and a rear electrode comprising a plurality of pixel electrodes; wherein the first adhesive layer is formed using an adhesive composition comprising polyurethane and a cationic polymeric dopant represented by Formula I or a polymerizable cationic dopant represented by Formula II. The electro-optic component may further comprise a second adhesive layer located between the conductive transparent layer and the electro-optic material layer. The second adhesive layer may also be formed using an adhesive composition comprising polyurethane and a cationic polymeric dopant represented by Formula I or a polymerizable cationic dopant represented by Formula II.

[0044] In another aspect, the present invention provides an electro-optic component comprising, in sequence: a conductive light-transmitting layer, an electro-optic material layer, a first adhesive layer, and a release sheet; wherein the first adhesive layer is formed using an adhesive composition comprising polyurethane and a cationic polymeric dopant represented by Formula I or a polymerizable cationic dopant represented by Formula II.

[0045] In another aspect, the present invention provides an electro-optic component comprising, in sequence: a first release sheet, a first adhesive layer, an electro-optic material layer, a second adhesive layer, and a second release sheet; wherein at least one of the first adhesive layer and the second adhesive layer is formed using an adhesive composition comprising polyurethane and a cationic polymeric dopant represented by Formula I or a polymerizable cationic dopant represented by Formula II.

[0046] Electro-optic components comprising an adhesive layer formed by the adhesive composition of the present invention exhibit improved electro-optic properties, especially at low temperatures.

[0047] The following detailed description describes other aspects and various non-limiting embodiments of the invention. In the event of conflicting and / or inconsistent disclosures in this specification and other documents incorporated by reference, this specification shall prevail. If two or more documents incorporated by reference contain conflicting and / or inconsistent disclosures, the document with the later effective date shall prevail. Brief description of the attached diagram

[0048] Various aspects and embodiments of this application will be described with reference to the following figures. It should be understood that the figures are not necessarily drawn to scale.

[0049] Figure 1 This is a schematic diagram of an electro-optic assembly comprising a conductive light-transmitting layer, an electro-optic material layer, a first adhesive layer, and a rear electrode layer comprising multiple pixel electrodes.

[0050] Figure 2 This is a schematic diagram of an electro-optic assembly comprising a conductive light-transmitting layer, a second adhesive layer, an electro-optic material layer, a first adhesive layer, and a rear electrode layer comprising multiple pixel electrodes.

[0051] Figure 3 This is a schematic diagram of an electro-optic assembly comprising a conductive light-transmitting layer, an electro-optic material layer comprising an electrophoretic medium, a first adhesive layer, and a rear electrode layer comprising multiple pixel electrodes.

[0052] Figure 4 This is a schematic diagram of an electro-optic assembly comprising a conductive light-transmitting layer, a second adhesive layer, an electro-optic material layer containing an electrophoretic medium, a first adhesive layer, and a rear electrode layer containing multiple pixel electrodes.

[0053] Figure 5 This is a schematic diagram of an electro-optic assembly (front panel laminate) comprising a conductive light-transmitting layer, an electro-optic material layer, a first adhesive layer, and a first release sheet.

[0054] Figure 6 This is a schematic diagram of an electro-optic assembly (double-sided release film) comprising a first release sheet, a first adhesive layer, an electro-optic material layer, a second adhesive layer, and a second release sheet.

[0055] Other aspects, embodiments, and features of the invention will become apparent from the following detailed description when considered in conjunction with the accompanying drawings.

[0056] Detailed Explanation

[0057] Adhesive compositions for laminated structures are well known. They are used to bond different layers of a laminated structure together. Such adhesive compositions may contain, for example, hot-melt adhesives and / or wet-apply adhesives, such as polyurethane-based adhesives. Generally, electro-optical components are laminated structures and include adhesive layers. The adhesive layers of electro-optical components must meet certain requirements regarding their mechanical, thermal, and electrical properties.

[0058] There are some issues with the selection of laminating adhesives for electro-optic displays. Because the laminating adhesive is typically located between electrodes that apply the electric field required to change the electrical state of the electro-optic medium, the conductivity of the adhesive can significantly affect the electro-optic performance of the display.

[0059] The volume resistivity of the laminating adhesive affects the total voltage drop across the electro-optic medium, a crucial factor in the medium's performance. The voltage drop across the electro-optic medium equals the voltage drop across the electrodes minus the voltage drop across the laminating adhesive. On one hand, if the adhesive layer's resistivity is too high, a considerable voltage drop occurs within the adhesive layer, requiring a higher voltage between the electrodes to generate the operating voltage drop at the electro-optic medium. Increasing the voltage across the electrodes in this way is undesirable because it increases power consumption and may require more complex and expensive control circuitry to generate and switch the increased voltage. On the other hand, if the adhesive layer's resistivity is too low, undesirable crosstalk will exist between adjacent electrodes (i.e., active matrix electrodes), or the device may simply short-circuit. Furthermore, because the volume resistivity of most materials decreases rapidly with increasing temperature, if the adhesive's volume resistivity is too low, the display's performance will change significantly with temperatures substantially above (or below) room temperature.

[0060] For these reasons, the resistivity values ​​of laminated adhesives have an optimal range for most electro-optic media, which varies with the resistivity of the electro-optic medium. The volume resistivity of the encapsulated electrophoretic medium is typically around 10⁻⁶. 10 The resistivity of the laminating adhesive is approximately 10 ohms-cm, and the resistivity of other electro-optic media is typically on the same order. Therefore, for good electro-optic performance, at the display's operating temperature of approximately 20°C, the volume resistivity of the laminating adhesive is preferably about 10 ohms-cm. 8 Ohm-cm to approximately 10 12 Ohm-cm, or about 10 9 Ohm-cm to approximately 10 11The range is ohm-cm. Preferably, the volume resistivity of the laminating adhesive will also change with temperature similarly to that of the electro-optic dielectric itself. This value corresponds to a measurement taken after one week of conditioning at 25°C and 50% relative humidity.

[0061] In addition to electrical properties, laminating adhesives must meet numerous mechanical and rheological standards, including adhesive strength, flexibility, ability to withstand lamination temperatures, and flowability. The number of commercially available adhesives that meet all relevant electrical and mechanical standards is limited.

[0062] One way to improve the electro-optic performance of electro-optic devices is to incorporate ionic dopants, such as inorganic or organic salts, including ionic liquids, into a binder composition. Dopants can also be incorporated into electro-optic material layers, which can also enhance low-temperature performance. For example, to improve the performance of commercially available polyurethane binder compositions, the compositions can be doped with salts or other materials. An example of such a dopant is tetrabutylammonium hexafluorophosphate. However, it has been found empirically that some binder compositions formulated with such dopants can damage active matrix backplanes, especially those including transistors made of organic semiconductors. Furthermore, it has been observed that many binder compositions are insensitive to such dopants, and the corresponding electro-optic components exhibit below-optimal switching performance at low temperatures.

[0063] This invention provides an adhesive composition for use in laminated structures comprising electro-optic components. The adhesive composition can be cured via various mechanisms such as thermal, chemical, and / or photo-activated curing. Depending on the curing mechanism, the adhesive composition may also contain other additives in addition to one or more polymers and cationic polymerizable dopants or polymerizable cationic dopants. The dopants disclosed herein can also be used in other parts of the electro-optic component, such as adhesives for electro-optic material layers. The adhesive composition (and / or binder composition) of this invention provides improved electro-optic properties, particularly at low temperatures.

[0064] The adhesive composition of the present invention can be prepared by mixing a polyurethane dispersion or solution or pure polyurethane with a cationic polymerizable dopant or with a polymerizable cationic dopant and other additives using equipment known in the art for mixing liquids.

[0065] The adhesive composition of the present invention comprises polyurethane and a cationic polymeric dopant represented by Formula I. Groups R3, R4, and R5 are independently alkyl or alkenyl groups having a chain having 1 to 30 carbon atoms, or -(CH2). bThe -Q2-R2 group, wherein b is 2 to 5; R1 and R2 are independently selected from hydrogen, alkyl groups having a chain of 1 to 30 carbon atoms, aryl groups, -OH, -SH, -NH2, -NHR1', and -NR1'R1"; Q1 and Q2 are independently selected from ethylene oxide, polyethylene oxide, propylene oxide, polypropylene oxide, and mixtures thereof, wherein polyethylene oxide has a total of 2 to 100 ethylene oxide units, and polypropylene oxide has 2 to 100 propylene oxide units; R1' and R1" are alkyl groups having a chain of 1 to 30 carbon atoms. Groups R3, R4, and R5 may also be alkyl groups having a chain of 6 to 22 carbon atoms or 10 to 18 carbon atoms. Groups R1 and R2 may also be independently selected from hydrogen and alkyl groups having a chain of 1 to 18 carbon atoms. Therefore, the molecular structure of the cationic polymeric dopant comprises a quaternary ammonium group and at least one polyether group. The counterion of the cationic polymer dopant is also important for the performance of the binder layer. It is a polyatomic anion containing at least two fluorine atoms. The polyatomic anion may contain at least three fluorine atoms.

[0066]

[0067] The number-average molecular weight of the cationic portion of the cationic polymer dopant in the adhesive composition can be from about 400 Daltons to about 25,000 Daltons, more preferably from about 500 Daltons to about 8,000 Daltons, even more preferably from about 700 Daltons to about 5,000 Daltons, and even more preferably from about 800 Daltons to about 2,000 Daltons. In this document, molecular weight values ​​correspond to the number-average molecular weight of the cationic substance of the cationic polymer dopant, excluding the polyatomic anionic counterion. That is, the molecular weight corresponds to the number-average molecular weight of a single cationic polymer substance containing atoms linked by covalent bonds present in the adhesive composition. Those skilled in the art will understand that the stoichiometry of the cationic-anionic portion of the cationic polymer dopant will vary depending on the positive:negative charge ratio of the substances involved.

[0068] The adhesive composition may contain about 0.3% to about 2% by weight, preferably about 0.4% to about 3% by weight, and more preferably about 0.5% to about 1% by weight of a cationic polymeric dopant, of the total solids of the adhesive composition. The total solids of the adhesive composition include all components of the adhesive composition except for one or more volatile solvents. In this document, the volatile solvent is a material with a boiling point below 250°C that does not polymerize under curing conditions.

[0069] The adhesive composition of the present invention may comprise polyurethane and cationic polymeric dopants, represented by formula IA.

[0070]

[0071] R1 and R2 are independently hydrogen, an alkyl group having a chain of 1 to 30 carbon atoms, an aryl group, -OH, -SH, -NH2, -NHR1', or -NR1'R1"; R6 and R7 are independently alkyl or alkenyl groups having a chain of 1 to 30 carbon atoms; Q1 and Q2 are independently selected from ethylene oxide, polyethylene oxide, propylene oxide, polypropylene oxide, and mixtures thereof, wherein the polyethylene oxide has a total of 2 to 100 ethylene oxide units, and the polypropylene oxide has 2 to 100 propylene oxide units. Groups R1 and R2 may also be alkyl groups having a chain of 1 to 22 carbon atoms or 6 to 18 carbon atoms. The number average molecular weight of the cationic moiety of the cationic polymeric dopant is from about 400 Daltons to about 25,000 Daltons; and Y n- The counter ion is a polyatomic anion containing at least two fluorine atoms; and n is 1 to 6. The cationic polymeric dopant of formula IA contains a quaternary ammonium group and two ether or polyether groups.

[0072] Examples of cationic polymeric dopants in adhesive compositions are represented by formula IB.

[0073]

[0074] R8 is selected from alkyl and alkenyl functional groups having 12 to 18 carbon atoms. In this example, the molecular structure of the cationic polymeric dopant comprises a quaternary ammonium salt, wherein the nitrogen of the quaternary ammonium salt has the following four substituents: (a) two polyether functional groups, (b) an ethyl group, and (c) an aliphatic alkyl / alkenyl chain. In the case where R6 is derived from animal fats, the material is an ionic liquid material and is supplied by Io-li-tec Nanomaterials under the trademark IoLiLyte T2EG. The hydrocarbon groups derived from animal fats comprise alkyl and / or alkenyl chains having 16 to 18 carbon atoms and a smaller amount of a mixture of alkyl and / or alkenyl chains having 14, 15, and 17 carbon atoms.

[0075] Another adhesive composition of the present invention comprises polyurethane and a polymerizable cationic dopant represented by Formula II. Group R9 may be a hydrogen or methyl group. Group R10 is an alkyl group having 1 to 10 carbon atoms or 1 to 5 carbon atoms; q is 1 to 5, Y n-The counter ion is a polyatomic anion containing at least two fluorine atoms, and n is 1 to 6. The counter ion may also be a polyatomic anion containing at least three fluorine atoms. As can be seen in Formula II, the molecular structure of the polymerizable cationic dopant comprises vinyl acrylate or vinyl methacrylate functional groups, imidazolium functional groups, and a polyatomic anionic counter ion containing at least two fluorine atoms. The monomer can be polymerized during the curing process via free radical polymerization to provide its homopolymer, or with other reactive monomers present in the adhesive composition via known methods, such as polymerization by UV light irradiation in the presence of a suitable photoinitiator, or polymerization by thermal excitation.

[0076]

[0077] The adhesive composition may contain about 0.05% to about 5% by weight of the total solids of the adhesive composition, preferably about 0.1% to about 3% by weight, more preferably about 0.5% to about 1.5% by weight of a polymerizable cationic dopant. The total solids of the adhesive composition include all components of the adhesive composition except for one or more volatile solvents. In this document, the volatile solvent is a material with a boiling point below 250°C that does not polymerize under curing conditions.

[0078] The number-average molecular weight of the cationic portion of the polymerizable cationic dopant in the adhesive composition can be from about 183 Daltons to about 415 Daltons, more preferably from about 190 Daltons to about 300 Daltons. In this document, molecular weight values ​​correspond to the number-average molecular weight of the cationic substance of the cationic polymeric dopant, excluding polyatomic anionic counterions. That is, the molecular weight corresponds to the number-average molecular weight of a single cationic polymeric substance containing atoms linked by covalent bonds present in the adhesive composition. Those skilled in the art will understand that the stoichiometry of the cationic-anionic portion of the cationic polymeric dopant will vary depending on the positive:negative charge ratio of the substances involved.

[0079] Examples of polymerizable cationic dopants in adhesive compositions are represented by formula IIA.

[0080]

[0081] Unrestricted examples of polyatomic anionic counterions of cationic polymerizable dopants and polymerizable cationic dopants include trifluoroacetate, trifluoromethanesulfonate, tetrafluoroborate, 1,1,2,2-tetrafluoroethanesulfonic acid, fluoroantimonic acid, hexafluorophosphate, hexafluorosilicic acid, nonafluorobutanesulfonate, tris(perfluoroalkyl)trifluorophosphate, 2,2,2-trifluoromethanesulfonyl-N-cyanoamide, and 2,2,2-trifluoro-N-[(trifluoromethyl)sulfonyl]acetyl Amines, heptadecafluorooctane sulfonic acid, 1,1,1-trifluoro-N-((trifluoromethyl)sulfonyl)methanesulfonamide, bis(perfluoroethylsulfonyl)amide, bis[(trifluoromethyl)sulfonyl]imide, bis(fluorosulfonyl)imide, fluorotrifluoromethylsulfonylimide, (fluorosulfonyl)(pentafluoroethanesulfonyl)imide, (trifluoromethylsulfonyl)(pentafluoroethanesulfonyl)imide, and (trifluoromethylsulfonyl)(nonafluorobutylsulfonyl)imide.

[0082] The adhesive composition of the present invention comprises polyurethane. The adhesive composition of the present invention may be in the form of a polyurethane solution or a polyurethane dispersion in an aqueous or non-aqueous medium.

[0083] In some embodiments, the adhesive composition is provided in the form of an aqueous polyurethane dispersion. For example, in some cases, the adhesive dispersion may be used directly in a coating method and / or as a solution of reactive monomers in the dispersion or solution of the adhesive to form the adhesive layer described herein. In some cases, the aqueous dispersion contains water, which may be removed after the adhesive has been deposited on one or more surfaces (e.g., via the application of heat).

[0084] The adhesive composition may comprise about 3% to about 60% by weight of the total solids of the adhesive composition, preferably about 15% to about 50% by weight, more preferably about 30% to about 40% by weight of polyurethane. The total solids of the adhesive composition include all components of the adhesive composition except for one or more volatile solvents. In this document, the volatile solvent is a material with a boiling point below 250°C that does not polymerize under curing conditions.

[0085] Polyurethanes are typically prepared via polymerization methods involving diisocyanates. Non-limiting examples of polyurethanes include polyether polyurethanes, polyester polyurethanes, polyether polyureas, polyureas, polyester polyureas, polyester polyureas, polyisocyanates (e.g., polyurethanes containing isocyanate bonds), and polycarbodiimides (e.g., polyurethanes containing carbodiimide bonds). Polyurethanes can be prepared using methods known in the art. Typically, polyurethanes are formed by reacting at least one diisocyanate compound with a secondary agent containing at least two groups capable of reacting with isocyanate groups. The secondary agent can be a diol or a polyol. The diol can be an oligomer having two or more reactive alcohol groups. Non-limiting examples of difunctional polyols include polyethylene glycol, polypropylene glycol (PPO), and polytetramethylene glycol. The secondary agent can be a diamine, a polyamine, or an agent having two or more thiol functional groups. For example, more than one type of diisocyanate compound can be used; more than one type of secondary agent can be used.

[0086] Diisocyanates can be linear, cyclic, or branched hydrocarbons, including aromatic, cycloaliphatic, and aliphatic hydrocarbons with two free isocyanate groups. Non-limiting examples of diisocyanate compounds include 4,4-methylene bis(cyclohexyl)isocyanate (H12MDI), α,α,α,α-tetramethylxylene diisocyanate, 3,5,5-trimethyl-1-isocyano-3-isocyanomethylcyclohexaneisophorone diisocyanate and its derivatives, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI) and its derivatives, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, isophorone diisocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, benzene 1,3-bis(1-isocyano-1-methylethyl), 1,5-naphthalene diisocyanate, phenylene diisocyanate, transcyclohexane-1,4-diisocyanate, and bitolylene diisocyanate. (diisocyanate), 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, dialkyldiphenylmethane diisocyanate and tetraalkyldiphenylmethane diisocyanate, 4,4'-dibenzyl diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, isomers of methylphenylene diisocyanate, 1-methyl-2,4-diisocyanocyclohexane, 1,6-diisocyano-2,2,4-trimethylhexane, 1,6-diisocyano-2,4,4-trimethylhexane, 1-isocyanomethyl-3-isocyanomethyl-3-isocyano-1,5,5-trimethylcyclohexane, diisocyanate and brominated diisocyanate The diisocyanate compound includes phosphorus-containing diisocyanates, 4,4'-diisocyanatophenylperfluoroethane, tetramethoxybutane-1,4-diisocyanate, butane-1,4-diisocyanate, hexane-1,6-diisocyanate, dicyclohexylmethane diisocyanate, cyclohexane-1,4-diisocyanate, ethylene diisocyanate, phthalic acid-bis-isocyanoethyl ester, and polyisocyanates containing reactive halogen atoms, such as 1-chloromethylphenyl-2,4-diisocyanate, 1-bromomethylphenyl-2,6-diisocyanate, and 3,3-bis-chloromethyl ether-4,4'-diphenyl diisocyanate. In some embodiments, the diisocyanate compound is 4,4-methylenebis(cyclohexylisocyanate).

[0087] Some polyurethanes can be formed using diols containing ionic groups (e.g., carboxylic acid groups). These ionic groups can be used to stabilize the polyurethane (e.g., when dispersed in water) and / or for crosslinking. Non-limiting examples of diols containing ionic groups include dimethylolpropionic acid (DMPA), dimethylolbutyric acid, dimethylolpentanoic acid, diethylolpropionic acid, diethylolbutyric acid, 1,4-dihydroxy-2-butanesulfonic acid, 1,5-dihydroxy-2-pentanesulfonic acid, 1,5-dihydroxy-3-pentanesulfonic acid, 1,3-dihydroxy-2-propanesulfonic acid, dimethylolethanesulfonic acid, N-methyldiethanolamine, N-ethyldiethanolamine, N-propyldiethanolamine, N,N-dimethyl-2-dihydroxymethylbutanamine, N,N-diethyl-2-dihydroxymethylbutanamine, and N,N-dimethyl-2-dihydroxymethylpropylamine. In some embodiments, the ionic group is a carboxylic acid group. Non-limiting examples of diols containing a carboxylic acid group include dimethylolpropionic acid, dimethylolbutyric acid, dimethylolvalerate, diethylolpropionic acid and diethylolbutyric acid, polyester glycols, and other polymeric carboxylic acid groups. In some embodiments, the diol containing the ionic group is dimethylolpropionic acid.

[0088] While polyurethane is provided as an exemplary adhesive material, those skilled in the art will be able to utilize the compositions and methods described herein in adhesives comprising other types of adhesives. In some embodiments, the adhesive comprises acrylic. In some embodiments, the adhesive comprises two or more types of adhesives (e.g., polyurethane and acrylic).

[0089] The adhesive compositions of the present invention can be formed by blending at least two components, which can be solutions or material dispersions in any combination of aqueous or solvent-based media. In some embodiments, the components can be formed by synthetic polymerization methods, wherein one component is polymerized in the presence of a second polymerizing component, or two polymers can be formed simultaneously. In some cases, the adhesive compositions can be formed by emulsifying polymerizable monomers in an adhesive dispersion, which is used directly in coating methods, and / or by using reactive monomers in a dispersion or solution of the adhesive. In some cases, the polymerization of the monomers can occur in a primary or secondary stage (i.e., curing) and can also contribute to filling ink surface pores and particle aggregation (e.g., if a dispersion is used).

[0090] The adhesive material may contain two or more reactive functional groups. The reactive functional groups may be terminal groups, along the main chain, or along a chain extending from the main chain.

[0091] Reactive functional groups generally refer to functional groups present in adhesives configured to react with one or more curing substances, such as crosslinking agents, chain extenders, etc. In some embodiments, the reactive functional group reacts with the curing substance to form a cured portion, such as crosslinking, thermoplastic bonding, or a bond between two types of adhesive materials. In some embodiments, the reactive functional group may react with the curing substance, such as a crosslinking agent, to form a crosslink. In some cases, the reactive functional group may be configured to react with another reactive functional group under specific conditions, such as within a specific temperature range. In some embodiments, the reactive functional group may react under specific conditions to subject the adhesive material to thermoplastic drying. Non-limiting examples of reactive functional groups include hydroxyl, carbonyl, aldehyde, carboxylic acid esters, amines, imines, imides, azides, ethers, esters, thiols (thiols), silanes, nitriles, urethanes, imidazoles, pyrrolidones, carbonates, acrylates, alkenyl groups, and alkynyl groups. Other reactive functional groups are also possible, and those skilled in the art will be able to select suitable reactive functional groups for use in dual-curing adhesives based on the teachings of this specification. Those skilled in the art will also understand that the curing steps described herein generally do not involve the formation of the adhesive material, such as the polymerization of the adhesive backbone like a polyurethane backbone, but rather further reactions of the adhesive material that cause it to crosslink, undergo thermoplastic drying, etc., resulting in significant changes to the mechanical properties, viscosity, and / or adhesiveness of the adhesive.

[0092] In some embodiments, the functional reactive groups react with the curing material in the presence of a stimuli, such as electromagnetic radiation (e.g., visible light, UV light, etc.), electron beams, high temperatures (e.g., those used during solvent extraction or condensation reactions), chemical compounds (e.g., thiols), and / or crosslinking agents. For example, an adhesive composition comprising vinyl acrylate monomers or oligomers can be polymerized on a substrate via UV irradiation in the presence of a photoinitiator. In the case of polymerizable cationic dopants of Formula II, the dopant can be polymerized together with the vinyl acrylate monomers or oligomers and become part of the same polymer.

[0093] In another embodiment, the adhesive composition may also include a crosslinking agent. The crosslinking agent may comprise a functional group selected from isocyanate groups, epoxy groups, hydroxyl groups, aziridines, amines, and combinations thereof. Non-limiting examples of crosslinking agents include homopolymers and copolymers of 1,4-cyclohexanediethanol diglycidyl ether (CHDDE), neopentyl glycol diglycidyl ether (NGDE), O,O,O-triglycidylglycerol (TGG), homopolymers and copolymers of glycidyl methacrylate, and N,N-diglycidylaniline. In some embodiments, the adhesive containing the crosslinking agent may be crosslinked upon exposure to the activation temperature of the crosslinking agent. The crosslinking agent may be present in the adhesive composition at a concentration of about 100 ppm to about 15,000 ppm by weight of the adhesive composition.

[0094] The adhesive composition of the present invention, comprising polyurethane and a cationic polymeric dopant or a polymerizable cationic dopant (represented by Formula I and Formula II, respectively), can be used to form an adhesive layer in an electro-optic component. The electro-optic component may sequentially include a conductive transparent layer, an electro-optic material layer in electrical contact with the conductive transparent layer, a first adhesive layer, and a backplane substrate. The backplane substrate includes a rear electrode comprising a plurality of pixel electrodes. The component is configured to apply a potential between the conductive transparent layer and the pixel electrodes. The electro-optic component may further include a second adhesive layer between the conductive transparent layer and the electro-optic material layer. The electro-optic component can be manufactured using a front-plate laminate (FPL) that sequentially includes a conductive transparent layer, an electro-optic material layer, a first adhesive layer, and a release sheet. The electro-optic component can also be manufactured using a double-sided release film that sequentially includes a first release sheet, a first adhesive layer, a conductive transparent layer, a second adhesive layer, and a second release sheet.

[0095] like Figure 1 As described, in some embodiments, the electro-optic component 100 includes a conductive light-transmitting layer (or front electrode) 110, an electro-optic material layer 120, and a rear electrode 140 containing a plurality of pixel electrodes. As shown above, the different layers of the component may be bonded together using an adhesive layer. Figure 1 In this process, the rear electrode 140 is adhered to the electro-optic material layer via the adhesive layer 130.

[0096] In some implementation schemes, such as Figure 2 As described, the electro-optic component 200 may contain more than one adhesive layer. Specifically, in this example, the rear electrode 240 is adhered to the electro-optic material layer 220 via adhesive layer 230, and the conductive light-transmitting layer 210 is adhered to the electro-optic material layer 220 via adhesive layer 235, wherein adhesive layer 235 may contain the same or different adhesive as adhesive layer 230.

[0097] Electro-optic components can be electrophoresis devices. For example... Figure 3 As described in the electro-optic component 300, the electro-optic material layer 325 may include a capsule 350 and an adhesive 360. The capsule 350 may encapsulate one or more particles that can be moved by an applied electric field across the electro-optic material layer 325. In some such embodiments, a conductive transparent layer 310 may be adjacent to the electro-optic material layer 325 and a rear electrode 340 may be adhered to the electro-optic material layer via a first adhesive layer 330. In exemplary embodiments, such as Figure 4As described in the electro-optic component 400, a rear electrode 440 can be adhered to an electro-optic material layer 425 via a first adhesive layer 430, and a conductive light-transmitting layer 410 can be adhered to the electro-optic material layer 425 via a second adhesive layer 435. The first adhesive layer 430 can be formed using the same or a different adhesive composition as the second adhesive layer 435.

[0098] The electro-optic component of the present invention may be a front panel laminate (FPL). In such a front panel laminate, the front panel may include a light-transmitting conductive layer intended to form a front electrode of the final display. The front panel may include a polymeric film or a similar support layer (e.g., which supports a relatively thin conductive layer and protects it from mechanical damage). In some such embodiments, the electro-optic component may include a release sheet that is removed before the front panel laminate is laminated to the back panel electrode to form the final display.

[0099] In an exemplary FPL implementation, such as Figure 5 As described in the electro-optic component 500, a conductive transparent layer 510 may be adjacent to an electro-optic material layer 520. It may allow a rear electrode 550 to be adhered to the electro-optic material layer 520 via a first adhesive layer 530. The first adhesive layer is formed using an adhesive composition comprising polyurethane and a cationic polymeric dopant represented by Formula I or a polymerizable cationic dopant represented by Formula II.

[0100] The electro-optic component of the present invention can be a double-sided release film. In another exemplary double-sided release film embodiment, such as Figure 6 As described in the electro-optic component 600, a first release sheet 601 is adhered to an electro-optic material layer 620 via a first adhesive layer 602. A second release sheet 604 is also adhered to the other side of the electro-optic material layer 620 via a second adhesive layer 603. The first adhesive layer 602 and the second adhesive layer 603 may be formed using the same or different adhesive compositions. At least one adhesive composition comprises polyurethane and a cationic polymerizable dopant represented by Formula I or a polymerizable cationic dopant represented by Formula II.

[0101] It should be understood that the adhesive compositions of the present invention can be used to form adhesive layers to adhere any type and number of layers to one or more other layers in an assembly, and the assembly may include one or more additional layers not shown in the figures. Additionally, although Figure 1-5 The invention describes specific types of electro-optic components, including encapsulated electrophoretic components and devices, but the adhesive compositions of the present invention can be used in a variety of electro-optic components, such as liquid crystals, frustrated internal reflection, and light-emitting diode components.

[0102] As described above, in some embodiments, the adhesive layer is located between the conductive transparent layer (or front electrode) and the rear electrode, and it can apply an electric field required to change the electrical state of the electro-optic medium of the electro-optic material layer. That is, the electrical properties of the adhesive (e.g., resistivity, conductivity) can alter the electric field applied to the electro-optic medium. If the adhesive resistivity is too high, a significant voltage drop may occur within the adhesive layer, necessitating an increase in the voltage across the electrodes. Increasing the voltage across the electrodes in this manner is undesirable, as it may increase the power consumption of the display and may require more complex and expensive control circuitry to handle the increased voltage. Conversely, if the adhesive layer extends continuously across the electro-optic component, contacting the electrode matrix, such as the electrode matrix in an active matrix display, the volume resistivity of the adhesive should not be too low; otherwise, lateral current conduction through the continuous adhesive layer may cause undesirable crosstalk between adjacent electrodes. Furthermore, since the volume resistivity of most materials decreases rapidly with increasing temperature if the adhesive volume resistivity is too low, the performance of the component is negatively affected at temperatures substantially above room temperature. Therefore, in some embodiments, the volume resistivity of the adhesive can be in the range of about 10⁸ ohm·cm to about 10¹² ohm·cm, or about 10⁹ ohm·cm to about 10¹¹ ohm·cm (e.g., at a component operating temperature of about 200°C). Other ranges of volume resistivity are also possible. This value corresponds to a measurement after one week of conditioning at 25°C and 50% relative humidity. The cured adhesive layer (e.g., after a first and second cure) can have a specific average coating weight. For example, the average coating weight of the adhesive layer can be from about 2 g / m² to about 25 g / m². In some embodiments, the average coating weight of the adhesive layer is at least about 2 g / m², at least about 4 g / m², at least about 5 g / m², at least about 8 g / m², at least about 10 g / m², at least about 15 g / m², or at least about 20 g / m². In some embodiments, the average coating weight of the adhesive layer is less than or equal to about 25 g / m², less than or equal to about 20 g / m², less than or equal to about 15 g / m², less than or equal to about 10 g / m², less than or equal to about 8 g / m², less than or equal to about 5 g / m², or less than or equal to about 4 g / m². Combinations of the above reference ranges are also possible (e.g., about 2 g / m² to about 25 g / m², about 4 g / m² to about 10 g / m², about 5 g / m² to about 20 g / m², about 8 g / m² to about 25 g / m²). Other ranges are also possible. The adhesive layer before curing may have a specific average wet coating thickness (e.g., such that the adhesive does not significantly alter the electrical and / or optical properties of the electro-optical component). For example, the average wet coating thickness of the adhesive layer may be in the range of about 1 micrometer to about 100 micrometers, about 1 micrometer to about 50 micrometers, or about 5 micrometers to about 25 micrometers.In some embodiments, the average wet coating thickness of the adhesive layer may be less than about 25 micrometers, less than about 20 micrometers, less than about 15 micrometers, less than about 12 micrometers, less than about 10 micrometers, or less than about 5 micrometers. In some embodiments (e.g., in embodiments where the adhesive is directly wet-applied to the electro-optic material layer), the average wet coating thickness of the adhesive layer may be from about 1 micrometer to about 50 micrometers, or from about 5 micrometers to about 25 micrometers, or from about 5 micrometers to about 15 micrometers. In some embodiments (e.g., in embodiments where the adhesive is coated onto a layer and then laminated to the electro-optic material layer), the average wet coating thickness of the adhesive layer may be from about 15 micrometers to about 30 micrometers, or from about 20 micrometers to about 25 micrometers. Other wet coating thicknesses are also possible.

[0103] It should be understood that the adhesive layer may cover the entire substrate, or the adhesive layer may cover only a portion of the substrate.

[0104] Furthermore, the adhesive layer can be applied as a laminate, which typically produces a thicker adhesive layer, or it can be applied as a topcoat, which typically produces a thinner layer than the laminate. The topcoat can utilize a dual-curing system, wherein a first curing occurs before the topcoat, allowing the adhesive to be applied to the surface (or another surface) of the electro-optic material layer, and a second curing occurs after the topcoat to cure the material. If the underside surface is rough and only a thin layer is applied, the topcoat can be rough, or the topcoat can be used to planarize the rough underside surface. Planarization can occur in a single step, wherein the topcoat is applied to planarize the rough surface, for example, by adding sufficient adhesive to fill any pores, making the surface smooth and minimizing the increase in total thickness. Alternatively, planarization can occur in two steps. A topcoat is applied to minimally coat the rough surface, and a second coating is applied to planarize it. In another alternative, the topcoat can be applied to a smooth surface.

[0105] Reference again Figure 3 (and 4), in some embodiments, the electro-optic component includes an electro-optic material layer 325, a capsule 350, and an adhesive 360. In some embodiments, the adhesive may also be an adhesive, as described above. For example, the adhesive may be polyurethane.

[0106] In some embodiments, the rear electrode comprises one or more electrode layers patterned to define pixels of the display. For example, one electrode layer may be patterned as an elongated row electrode, and a second electrode layer may be patterned as an elongated column electrode extending at right angles to the row electrode, the pixel being defined by the intersection of the row and column electrodes. Alternatively, in some embodiments, one electrode layer has the form of a single continuous electrode, and the second electrode layer is patterned as a pixel electrode matrix, each defining a pixel of the display. In another type of electro-optic display intended for use with a stylus, the printhead or similar movable electrode is separate from the display, only one of these layers adjacent to the electro-optic material layer contains electrodes, and layers on the opposite side of the electro-optic material layer are generally protective layers intended to prevent damage to the electro-optic material layer by the movable electrode.

[0107] Reference again Figure 1 , 2 3, 4, and 5, the conductive light-transmitting layer may comprise a polymeric film or similar support layer (e.g., which supports the relatively thin light-transmitting electrodes and protects the relatively fragile electrodes from mechanical damage), and a back electrode (where applicable), which comprises a support portion and a plurality of pixel electrodes (e.g., which define individual pixels of the display). In some cases, the backplate may further comprise nonlinear devices (e.g., thin-film transistors) and / or other circuitry for generating the potentials required to drive the display on the pixel electrodes (e.g., to switch each pixel to the display state required to provide the desired image on the display).

[0108] For convenience, certain terms used in the specification, examples, and appended claims are listed herein. Definitions of specific functional groups and chemical terms are detailed below. For the purposes of this invention, chemical elements are identified according to the CAS version of the periodic table of elements on the cover of the 75th edition of the Handbook of Chemistry and Physics, and specific functional groups are generally defined as described therein. Furthermore, the general principles of organic chemistry and the relationship between specific functional groups and reactivity are described in Thomas Sorrell's Organic Chemistry, University Science Books, 2nd edition, Sausalito: 2006.

[0109] As used herein, the term "aliphatic" includes saturated and unsaturated, non-aromatic, straight-chain (i.e., unbranched), branched, acyclic, and cyclic (i.e., carbocyclic) hydrocarbons, optionally substituted with one or more functional groups. Those skilled in the art will understand that "aliphatic" is intended herein to include, but is not limited to, alkyl, alkenyl, ynyl, cycloalkyl, cycloalkenyl, and cycloynyl moieties. Therefore, the term "alkyl" as used herein includes straight-chain, branched, and cyclic alkyl groups. Similar convention applies to other superordinate terms such as "alkenyl," "ynyl," etc. Furthermore, the terms "alkyl," "alkenyl," "ynyl," etc., as used herein encompass substituted and unsubstituted groups. In some embodiments, the term "aliphatic" as used herein is used to refer to those aliphatic groups (cyclic, acyclic, substituted, unsubstituted, branched, or unbranched) having 1-30 carbon atoms, unless otherwise indicated. Aliphatic substituents include, but are not limited to, any substituents described herein that result in the formation of a stable moiety (e.g., aliphatic, alkyl, alkenyl, alkynyl, heteroaliphatic, heterocyclic, aryl, heteroaryl, acyl, oxo, imino, thiooxo, cyano, isocyano, amino, azide, nitro, hydroxyl, thiol, halogen, aliphatic amino, heteroaliphatic amino, alkylamino, heteroalkylamino, arylamino, heteroarylamino, alkylaryl, arylalkyl, aliphatic oxy, heteroaliphatic oxy, alkoxy, heteroalkoxy, aryloxy, heteroaryloxy, aliphatic sulfoxy, heteroaliphatic sulfoxy, alkyl sulfoxy, heteroalkyl sulfoxy, aryl sulfoxy, heteroaryl sulfoxy, acyloxy, etc., each of which may be further substituted or may not be further substituted).

[0110] The term "aromatic" is used in its general sense in the art and refers to an aromatic carbocyclic group having a monocyclic (e.g., phenyl), polycyclic (e.g., biphenyl), or at least one of which is an aromatic polycyclic ring (e.g., 1,2,3,4-tetrahydronaphthyl, naphthyl, anthraceneyl, or phenanthrene). That is, at least one ring may have a conjugated π-electron system, while the other adjacent rings may be cycloalkyl, cycloalkenyl, cycloynyl, aryl, and / or heterocyclic groups.

[0111] The term "aryl" has its general meaning as used in the art and refers to an optionally substituted aromatic carbocyclic group having a monocyclic (e.g., phenyl), polycyclic (e.g., biphenyl), or at least one of which is an aromatic polycyclic ring (e.g., 1,2,3,4-tetrahydronaphthyl, naphthyl, anthraceneyl, or phenanthrene). That is, at least one ring may have a conjugated π-electron system, while the other adjacent rings may be cycloalkyl, cycloalkenyl, cycloynyl, aryl, and / or heterocyclic. As described herein, the aryl group may optionally be substituted. Substituents include, but are not limited to, any of the aforementioned substituents, i.e., substituents listed in the aliphatic moiety disclosed herein, or in other parts of the disclosure herein, resulting in the formation of a stable compound. In some cases, the aryl group is a stable monocyclic or polycyclic unsaturated moiety having preferably 3-14 carbon atoms, each of which may be substituted or unsubstituted.

[0112] The terms “alkenyl” and “alkynyl” are used in their general sense in the art and refer to unsaturated aliphatic groups of similar length to the alkyl groups described above and which may replace the alkyl groups, but which each contain at least one double or triple bond.

[0113] The counterion Y of the cation dopant represented by formulas I and II n- The n-exponent represents the negative charge of the counter ion. In other words, if n is 1, the charge of the counter ion is -1; when n is 2, the charge of the counter ion is -2, and so on.

[0114] These and other aspects of the invention will be further understood when considering the following embodiments, which are intended to illustrate certain specific implementations of the invention but are not intended to limit the scope of the invention as defined by the claims. Example

[0115] A mixture of polyurethane dispersion and ion dopant. The following portions are by weight.

[0116] Comparative Example 1A: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.0500 parts of 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM PF6) was prepared.

[0117] Comparative Example 1B: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.0340 parts of 1-butyl-3-methylimidazolium dicyandiamide (BMIM DCN) was prepared.

[0118] Comparative Example 1C: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.0373 parts of 1-butyl-3-methylimidazolium boron tetrafluoride (BMIM BF4) was prepared.

[0119] Example 1D1: A mixture was prepared consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.0500 parts of a compound represented by formula IA, supplied by Io-li-tec Nanomaterials under the trademark IoLiLyte T2EG.

[0120] Example 1D2: A mixture was prepared consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.2000 parts of a compound represented by formula IA, supplied by Io-li-tec Nanomaterials under the trademark IoLiLyte T2EG.

[0121] Example 1D3: A mixture was prepared consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.3500 parts of a compound represented by formula IA, supplied by Io-li-tec Nanomaterials under the trademark IoLiLyte T2EG.

[0122] Example 1D4: A mixture was prepared consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.5000 parts of a compound represented by formula IA, supplied by Io-li-tec Nanomaterials under the trademark IoLiLyte T2EG.

[0123] Example 1D5: A mixture was prepared consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.6230 parts of a compound represented by formula IA, supplied by Io-li-tec Nanomaterials under the trademark IoLiLyte T2EG. NMR experiments confirmed that the ion content of the polymeric dopant in this example was equal to that of the dopant in Comparative Example 1A1. The NMR method is described below.

[0124] Comparative Example 1E: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.0500 parts of 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM PF6) was prepared. A stoichiometric amount of carbodiimide crosslinking agent (XL702 supplied by Picassian) was added (molar ratio of carbodiimide to the carboxylic acid functional group of the polyurethane 1:1).

[0125] Comparative Example 1F: A mixture was prepared consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.6405 parts of a compound represented by formula IA, but with ethyl sulfate as the counterion. As confirmed by NMR spectroscopy, the ion content of the polymeric dopant in this example was equal to that of the dopant in Comparative Example 1A. A stoichiometric amount of carbodiimide crosslinking agent (XL702 supplied by Picassian) was added (molar ratio of carbodiimide to carboxylic acid functional groups of polyurethane 1:1).

[0126] Example 1G: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.6405 parts of a compound represented by formula IA was prepared. As confirmed by NMR experiments, the ion content of the polymeric dopant in this example was equal to that of the dopant in Comparative Example 1A. A stoichiometric amount of carbodiimide crosslinking agent (XL702 supplied by Picassian) was added (molar ratio of carbodiimide to carboxylic acid functional groups of polyurethane 1:1).

[0127] Example 1H1: A mixture consisting of 286 g of polyurethane dispersion A (35% solids content) and 0.0500 g of tetrabutylammonium hexafluorophosphate (Bu4N PF6) was prepared.

[0128] Example 1H2: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.1000 parts of tetrabutylammonium hexafluorophosphate (Bu4N PF6) was prepared.

[0129] Example 1H3: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.1500 parts of tetrabutylammonium hexafluorophosphate (Bu4N PF6) was prepared.

[0130] Example 1H4: A mixture consisting of 286 parts of polyurethane dispersion A (35% solids content) and 0.2000 parts of tetrabutylammonium hexafluorophosphate (Bu4N PF6) was prepared.

[0131] Electro-optic components were constructed using adhesive compositions from Comparative Examples 1A, 1B, 1C, 1E, 1F, 1H1, 1H2, 1H3, 1H4, and Examples 1D1, 1D2, 1D3, 1D4, 1D5 and 1G as described in Example 2 below.

[0132] Construction of Comparative Example 2A - Component: A three-layer electro-optic component was constructed as follows: (a) an electro-optic material layer was coated onto a low-energy release sheet; the electro-optic material layer contained encapsulated electrophoretic media having negatively charged white particles and positively charged black particles suspended in a hydrocarbon suspension. The encapsulation was retained within a polymeric adhesive; (b) then, the adhesive composition of Comparative Example 1A was wet-coated onto the surface of the electro-optic material layer; (c) the coating was dried in a cross-draft oven; and (d) the dried coating was adhered to the backplane electrode. The thickness of the adhesive layer was approximately 40 micrometers. After removing the low-energy release sheet, the exposed side of the electro-optic material layer was attached to the front panel electrode to provide an electro-optic display, and equilibrated at 25°C and 50% relative humidity for 5 days.

[0133] Comparative Example 2B: Electro-optical assembly using the adhesive composition from Comparative Example 1B.

[0134] Comparative Example 2C: Electro-optical assembly using the adhesive composition from Comparative Example 1C.

[0135] Example 2D1: Electro-optical assembly using the adhesive composition from Example 1D1.

[0136] Example 2D2: Electro-optical assembly using the adhesive composition from Example 1D2.

[0137] Example 2D3: Electro-optical assembly using the adhesive composition from Example 1D3.

[0138] Example 2D4: Electro-optical assembly using the adhesive composition from Example 1D4.

[0139] Example 2D5: Electro-optical assembly using the adhesive composition from Example 1D5.

[0140] Comparative Example 2E: Electro-optical assembly using an adhesive composition from Comparative Example 1E.

[0141] Comparative Example 2F: Electro-optical assembly using the adhesive composition from Comparative Example 1F.

[0142] Example 2G: Electro-optical assembly using the adhesive composition from Example 1G.

[0143] Comparative Example 2H1: An electro-optical assembly using an adhesive composition from Comparative Example 1H1.

[0144] Comparative Example 2H2: An electro-optical assembly using an adhesive composition from Comparative Example 1H2.

[0145] Comparative Example 2H3: An electro-optical assembly using an adhesive composition from Comparative Example 1H3.

[0146] Comparative Example 2H4: An electro-optical assembly using an adhesive composition from Comparative Example 1H4.

[0147] Ion content determined by NMR spectroscopy: The ion content of dopants in the adhesive composition is determined by... 1 The determination was performed using ¹H-NMR spectroscopy. Specifically, a known amount of phenanthrene was mixed into a known amount of the adhesive composition. The mixture was dissolved in CDCl₃ to obtain the resulting solution. 1 ¹H-NMR spectroscopy. The ion content of the dopant is measured by integrating the corresponding dopant peak with respect to the phenanthrene peak.

[0148] Optical measurement method: The electro-optic properties of each electro-optic component were measured using a PR-650 SpectraScan colorimeter. The electro-optic component was repeatedly driven to its white and black extreme states using an electric field. It was then driven to a white or black display state, and its reflectance was measured via the colorimeter. The measurements were repeated at different temperatures.

[0149] The colorimeter measurement report shows the reflectance value L*. L* represents the optical switching performance of the electro-optic device's effectiveness (where L* follows the general CIE definition):

[0150] L* = 116(R / R0) 1 / 3 -16,

[0151] Where R is the reflectance and R0 is the standard reflectance value.

[0152] The contrast ratio (CR) of an electro-optic device is the ratio of its reflectance in a white state to its reflectance in a dark state. In other words, contrast ratio is expressed by the following formula:

[0153] CR=R WS / R DS

[0154] Where R WS The reflectivity and R of the device in its white state DS The reflectance of the device in the dark state is denoted as .

[0155] Contrast is determined by R WS With R DS The reflectance was measured and determined using the above equation. More specifically, R WS The reflectance in the white state was measured using a Macbeth spectrophotometer (SpectroEye supplied by GretagMacbeth) after a 15-volt voltage was applied between the electrodes of the apparatus for 0.4 seconds. The reflectance in the dark state was then measured after switching the poles and applying a 15-volt voltage between the electrodes of the apparatus for 0.4 seconds. Higher contrast was desired.

[0156] Table 1 shows the evaluation results of the electro-optic properties of the electro-optic component at 0°C. The adhesive composition comprises uncrosslinked polyurethane.

[0157] Table 2 shows the evaluation results of the electro-optic properties of the electro-optic component at 0°C. The adhesive composition comprises crosslinked polyurethane.

[0158] Table 3 shows the evaluation results of the electro-optic properties of the electro-optic component at 25°C. The adhesive composition comprises crosslinked polyurethane.

[0159] The value represents L* (brightness value) in white (WS) and black (DS) states. It is also the difference DR between L* for the corresponding display at the same temperature between WS and DS.

[0160] Table 1: Optical performance of the electro-optical assembly at 0°C. The adhesive composition of the adhesive layer comprises uncrosslinked polyurethane.

[0161]

[0162] Table 2: Optical performance of the electro-optical assembly at 0°C. The adhesive composition of the adhesive layer comprises cross-linked polyurethane.

[0163]

[0164] Table 3: Optical performance of the electro-optical assembly at 25°C. The adhesive composition of the adhesive layer comprises cross-linked polyurethane.

[0165]

[0166] A higher L* value indicates more light is emitted to display the appearance of the state. Therefore, a high value is preferred for the white state (WS), while a low value is preferred for the black state (DS). A larger DR corresponds to better optical performance. The data indicates that embodiments 2D5 and 2G of the present invention exhibit better electro-optical performance at low temperatures compared to comparative examples 2A1, 2B, 2C, 2E, and 2F. As mentioned above, comparative examples 2A1, 2B, 2C, and 2E contain cationic dopants. Comparative example 2F contains cationic polymeric dopants but has non-fluorinated counterions. Embodiments 2D5 and 2G of the present invention contain cationic polymeric dopants having polyatomic counterions containing at least two fluorine atoms. Furthermore, the ion content is similar in all embodiments.

[0167] Comparative Example 3A: A mixture consisting of 330 g of a polyurethane dispersion (30% solids content) forming an aqueous film, 1.0 part of 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM PF6) dissolved in 1 part of N-methylpyrrolidone, and 0.05 part of 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO) photoinitiator was prepared.

[0168] Example 3B: A mixture was prepared consisting of 330 parts of a polyurethane dispersion (30% solids) used in Example 3A for forming an aqueous film, 0.1 parts of a compound of formula IIA dissolved in 1 part of N-methylpyrrolidone, and a photoinitiator. The compound of formula IIA was synthesized by the reaction of 2-bromoethyl acrylate with 1-ethyl-1H-imidazolium, as described in Hong Chen et al., “Polymerized Ionic Liquids: The Effect of Random Copolymer Composition on Ion Conduction” (Macromolecules), 2009, 42, 4809-4816.

[0169] Comparative Example 4A: Construction of an electro-optic component: A three-layer electro-optic component was constructed by: (a) coating an electro-optic material layer onto a low-energy release sheet; the electro-optic material layer comprising an encapsulated electrophoretic medium having negatively charged white particles and positively charged black particles suspended in a hydrocarbon suspension. The encapsulation was retained within a polymeric adhesive; (b) then, the adhesive composition of Comparative Example 3A was wet-applied to the surface of the electro-optic material layer; (c) the coating was exposed to UV light to cure the polymer; and (d) the dried coating was adhered to the backplate electrode. The thickness of the adhesive layer was approximately 40 micrometers. After removing the low-energy release sheet, the exposed side of the electro-optic material layer was attached to the front plate electrode to provide an electro-optic display, and equilibrated at 25°C and 50% relative humidity for 5 days.

[0170] Comparative Example 4A: An electro-optical assembly using an adhesive composition from Comparative Example 3A.

[0171] Example 4B: Electro-optical assembly using the adhesive composition from Example 3B.

[0172] The electro-optic properties of the electro-optic components of Examples 4A and 4B were measured at 0°C as described above (optical measurement method).

[0173] Table 4 shows the evaluation results of the electro-optic properties of the electro-optic component at 0°C.

[0174] Comparative Example 4A 51.5 3 Example 4B 67.0 12.5

[0175] The data indicates that, compared to Comparative Example 4A (containing non-polymerizable dopants), Example 4B of the present invention (containing polymerizable cationic dopants) exhibits better electro-optic performance at low temperatures.

[0176] Unwilling to be bound by theory, dopants existing in the binder layer in the form of small molecules may diffuse and move within the layer and separate within their own phase or domain. This could produce binder layers with low and high conductivity domains and increase the overall volume resistivity of the binder layer, resulting in reduced electro-optic switching performance of the electro-optic component. Such dopant separation is less likely to occur when using polymeric dopants, which have significantly lower mobility and are less likely to diffuse through the binder layer.

Claims

1. An electro-optical component, comprising: The device comprises a conductive transparent layer, an electro-optic material layer, a first adhesive layer, and a rear electrode, wherein the first adhesive layer is formed of an adhesive composition comprising polyurethane and a cationic polymeric dopant, the cationic polymeric dopant being represented by formula IA. Formula IA in R1 and R2 are independently selected from hydrogen, alkyl groups having chains of 1 to 30 carbon atoms, aryl groups, -OH, -SH, -NH2, -NHR1' and -NR1'R1''; R6 and R7 are independently alkyl or alkenyl groups having chains of 1 to 30 carbon atoms; Q1 and Q2 are independently selected from ethylene oxide, polyethylene oxide, propylene oxide, polypropylene oxide and mixtures thereof, wherein the polyethylene oxide has a total of 2 to 100 ethylene oxide units and the polypropylene oxide has 2 to 100 propylene oxide units. R1' and R1'' are alkyl groups with chains having 1 to 30 carbon atoms; The number-average molecular weight of the cationic portion of the cationic polymeric dopant is between 400 Daltons and 25,000 Daltons. and Y n- As a counter ion, it is a polyatomic anion containing at least two fluorine atoms; where n is 1 to 6. Furthermore, the DR of the electro-optic component at 0°C is greater than that of the same electro-optic component at 0°C using the same adhesive composition but having non-fluorinated counterions, where DR represents the difference in brightness values ​​between the white and black states.

2. The electro-optical assembly according to claim 1, wherein the adhesive composition is in the form of a polyurethane solution or polyurethane dispersion in an aqueous medium.

3. The electro-optical assembly according to claim 1, wherein the polyatomic anion comprises at least three fluorine atoms.

4. The electro-optic component of claim 1, wherein the adhesive composition comprises 0.3% to 3% by weight of a cationic polymeric dopant based on the total solid weight of the adhesive composition.

5. The electro-optical assembly of claim 1, wherein the adhesive composition further comprises a material selected from polyacrylate, polymethacrylate, vinyl acrylate, vinyl methacrylate, and mixtures thereof.

6. The electro-optical assembly of claim 1, wherein the adhesive composition further comprises a crosslinking agent.

7. The electro-optic component of claim 6, wherein the crosslinking agent comprises a functional group selected from isocyanate groups, epoxy groups, hydroxyl groups, aziridine groups, amines, and combinations thereof.

8. The electro-optic component according to claim 1, wherein the counterion Y of the cationic polymer dopant is... n- Derived from trifluoroacetate, trifluoromethylsulfonate, tetrafluoroborate, 1,1,2,2-tetrafluoroethanesulfonic acid, fluoroantimony, hexafluorophosphate, hexafluorosilicic acid, nonafluorobutanesulfonate, tri(perfluoroalkyl)trifluorophosphate, 2,2,2-trifluoromethylsulfonyl-N-cyanoamide, 2,2,2-trifluoro-N-[(trifluoromethyl)sulfonyl]acetamide, heptadecafluorooctanesulfonic acid, 1,1,1-trifluoro-N-((trifluoromethyl)sulfonyl)methanesulfonamide, bis(perfluoroethylsulfonyl)amide, bis[(trifluoromethyl)sulfonyl]imide, bis(fluorosulfonyl)imide, (fluorosulfonyl)(pentafluoroethanesulfonyl)imide, (trifluoromethylsulfonyl)(pentafluoroethanesulfonyl)imide, and (trifluoromethylsulfonyl)(nonafluorobutylsulfonyl)imide.

9. The electro-optic component according to claim 1, wherein the cationic polymeric dopant is represented by formula IB. Formula IB R8 is selected from alkyl and alkenyl functional groups having 12 to 18 carbon atoms.

10. The electro-optic component of claim 1, wherein the electro-optic component further comprises a second adhesive layer located between the conductive light-transmitting layer and the electro-optic material layer, wherein the second adhesive layer is also formed using the adhesive composition.

11. The electro-optic assembly of claim 1, wherein the electro-optic material layer comprises a capsule and an adhesive, and wherein the capsule contains one or more particles that are movable upon application of an electric field across the electro-optic material layer.

Citation Information

Patent Citations

  • Electrophoretic display

    US20150005720A1

  • Magnetophoretic display assembly and driving scheme

    US20150277160A1

  • Smart medication device

    US20160012710A1

  • Method and apparatus for providing a dielectrophoretic display of visual information

    US4418346A

  • Highlight color twisting ball display

    US5760761A